2017
DOI: 10.1155/2017/1671607
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Interferons in Pregnant Women with Dengue Infection: Protective or Dangerous Factors

Abstract: Dengue infection is a serious public health problem in tropical and subtropical areas. With the recent outbreaks of Zika disease and its reported correlation with microcephaly, the large number of pregnancies with dengue infection has become a serious concern. This review describes the epidemiological characteristics of pregnancy with dengue and the initial immune response to dengue infection, especially in IFNs production in this group of patients. Dengue is much more prevalent in pregnant women compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In this work, we provide evidence that immune and serum metal ion responses in third-trimester pregnant women infected with SARS-CoV-2 vary according to the severity of the disease. Clinical manifestations in pregnant women with COVID-19 range from asymptomatic to severe ( Sevilla-Montoya et al, 2021 ); furthermore, some studies have described that the infection triggers a peripheral maternal inflammatory response ( Zhang et al, 2017 ; Cornish et al, 2020 ; Goldstein et al, 2020 ), and changes in metal ion concentrations ( Kilbride et al, 1999 ; Sangaré et al, 2014 ). Here, we have bridged these observations by studying the systemic cytokine and metal ion profile in asymptomatic and symptomatic women, and including a more significant number of severe cases than in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we provide evidence that immune and serum metal ion responses in third-trimester pregnant women infected with SARS-CoV-2 vary according to the severity of the disease. Clinical manifestations in pregnant women with COVID-19 range from asymptomatic to severe ( Sevilla-Montoya et al, 2021 ); furthermore, some studies have described that the infection triggers a peripheral maternal inflammatory response ( Zhang et al, 2017 ; Cornish et al, 2020 ; Goldstein et al, 2020 ), and changes in metal ion concentrations ( Kilbride et al, 1999 ; Sangaré et al, 2014 ). Here, we have bridged these observations by studying the systemic cytokine and metal ion profile in asymptomatic and symptomatic women, and including a more significant number of severe cases than in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Immunologic changes that occur in mid-to-late pregnancy could lead to an increase in the risk for severe dengue if infections occur during pregnancy (9,36,37). In our study, women were screened mainly during the second and third trimesters because the woman usually come for antenatal care during that period.…”
Section: Discussionmentioning
confidence: 99%
“…Belonging to the same flavivirus genus, DENV and ZIKV share similarities beyond phylogeny, including host immune responses. Proteins of the type I IFN subgroup (including IFN- α, β, ε, τ, and δ) exhibited contradictory roles in DENV pathogenesis, during which certain proteins were upregulated compared to other that were reduced in infected patients [ 78 , 79 ]. For type II IFNs, elevated serum levels of dengue patients were associated with higher chances of experiencing increased severity of disease [ 79 , 80 , 81 , 82 , 83 ].…”
Section: Host Cell Restriction Factors That Limit Zikv Replicationmentioning
confidence: 99%
“…Proteins of the type I IFN subgroup (including IFN- α, β, ε, τ, and δ) exhibited contradictory roles in DENV pathogenesis, during which certain proteins were upregulated compared to other that were reduced in infected patients [ 78 , 79 ]. For type II IFNs, elevated serum levels of dengue patients were associated with higher chances of experiencing increased severity of disease [ 79 , 80 , 81 , 82 , 83 ]. In vitro studies of type III IFNs induction following DENV infection demonstrated that IFN-λ has the inhibitory potential to control DENV replication [ 84 ].…”
Section: Host Cell Restriction Factors That Limit Zikv Replicationmentioning
confidence: 99%